2018
DOI: 10.1016/j.cmi.2017.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Severe fever with thrombocytopenia syndrome-associated encephalopathy/encephalitis

Abstract: Objectives: Severe fever with thrombocytopenia syndrome (SFTS) virus has a variety of central nervous system (CNS) manifestations. However, there are limited data regarding SFTS-associated encephalopathy/encephalitis (SFTSAE) and its mechanism. Methods: All patients with confirmed SFTS who underwent cerebrospinal fluid (CSF) examination due to suspected acute encephalopathy were enrolled in three referral hospitals between January 2013 and October 2016. Real-time RT-PCR for SFTS virus and chemokine/cytokines l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(60 citation statements)
references
References 22 publications
5
52
3
Order By: Relevance
“…In fact, overexpression of MCP-1 in the CNS clearly has an important role in viral encephalitis through the recruitment of monocytes, facilitating virus invasion into the brain. 18,19 However, similar results with our study, that is, only increased chemokines including MCP-1 without virus invasion, have been reported in other viralassociated encephalopathies. 20,21 In our R þ Wþ cases, rotavirus might not function in the CNS directly because neither pleocytosis nor virus was detected in the CSF.…”
Section: Discussionsupporting
confidence: 92%
“…In fact, overexpression of MCP-1 in the CNS clearly has an important role in viral encephalitis through the recruitment of monocytes, facilitating virus invasion into the brain. 18,19 However, similar results with our study, that is, only increased chemokines including MCP-1 without virus invasion, have been reported in other viralassociated encephalopathies. 20,21 In our R þ Wþ cases, rotavirus might not function in the CNS directly because neither pleocytosis nor virus was detected in the CSF.…”
Section: Discussionsupporting
confidence: 92%
“…Most risk factors for encephalopathy were consistent with the aforementioned factors related to poor prognosis. In addition, Park et al reported that CSF analysis exhibited glucose and protein levels within the normal range, an increase in cell count in the CSF was not remarkable, and the SFTSV genome was positive in 75% of cases [13]. These findings, along with the findings in this study, may be an important piece of information to advance our understanding of the pathophysiological mechanisms of encephalopathy in SFTS patients.…”
Section: Resultssupporting
confidence: 70%
“…Patients with SFTS are prone to develop encephalopathy [12,13]. Cui et al reported that 19% of patients with SFTS developed encephalopathy, and of these, the mortality rate was 44.7% [12].…”
Section: Resultsmentioning
confidence: 99%
“…We started PE from hospital day (HD) 1 and performed it a total of four times for about 120 minutes per session using a Cobe spectra (Terumo BCT, Lakewood, CO) because approximately 60-70% of the substances present in plasma are removed for each 1-1.5 plasma volumes exchanged, and more than 90% of substances can be removed when PE is performed more than three times. 5 We analyzed 18 cytokines and chemokines in his serum, as described previously, 6 and the levels of interferon (IFN)-α and inducible protein (IP)-10 significantly decreased after the start of PE ( Figure 1 and Supplemental Figure 1). However, even after the fourth PE, when the level of IP-10 was further reduced from 6,427.8 pg/mL (HD 1) to 5,040.73 pg/mL (HD 3), the patient's consciousness had deteriorated further to GCS score 9 and there was no change in serum viral load ( Figure 1).…”
Section: The Studymentioning
confidence: 99%